More Attacks and Analgesic Use in Old Age: Self-Reported Headache Across the Lifespan in a German Sample - Müller, Britta (Front Neurol, 2019)
Background: Reliable population-based data on the prevalence and characteristics of primary headache across the lifespan are essential. However, robust data are lacking. Methods: We utilized questionnaire data from a random general population sample in Germany, that comprised 2,478 participants aged ≥14 years. A standardized questionnaire addressing headache and headache treatment was filled in during the face-to-face survey. Results: The 6-month prevalence of self-reported headache in the total sample amounted to 39.0% (known diagnosis of migraine 7.2%; tension-type headache 12.4%; another diagnosis or unknown diagnosis 23.4%). Age-specific prevalence rates were 37.9% (14–34 years), 44.6% (35–54 years), 38.5% (55–74 years), and 26.9% (≥75 years). Compared to age group 14–34, participants aged 35–54 were more (OR = 1.29, 95%-CI 1.05–1.60, p = 0.018) and those aged ≥75 were less (OR = 0.55, 95%-CI 0.40–0.76, p < 0.001) likely to have any headache. Of the participants with headache, 79.5% reported headache on <4 days per month, 15.6% on 4–14 days per month and 4.9% on >14 days per month. The frequency of headache did not differ significantly between age groups in men [[Formula: see text] = 1.45, p > 0.05], but in women [[Formula: see text] = 21.57, p < 0.001]: women aged ≥75 years were over-represented in the group reporting 4–14 headache days per month. The analgesic use (days per month) differed significantly between age groups among participants with headache on <4 days per month and on >14 days per month: 1.8 (14–34 years), 2.5 (35–54 years), 3.2 (55–74 years), and 3.4 (≥75 years), respectively 7.9 (14–34 years), 11.4 (35–54 years), 18.4 (55–74 years), and 22.8 (≥75 years). Conclusions: In general, the prevalence of headache decreases with age. However, older women suffer from more frequent attacks and older participants take analgesics on more days per month than younger participants. This might put them at risk of medication overuse which may lead to medication overuse headache. More research is needed to understand these specifics in headache frequency and treatment behavior in older people.